The Analysis of the Implementation of the Dealer Management System (DMS) at PT X - Kudu, Diza Izallia Ananda Putri; Puji Wahono; Rizki Firdausi Rachmadania (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Dealer Management System (DMS) is a management information system that is very useful for increasing the efficiency and productivity of automotive company administration. In current technological developments in the automotive industry, efforts to implement digitalization systems in a business industry continue to be carried out and developed. The implementation of the Dealer Management System (DMS) illustrates changes to modern work processes by utilizing technological developments. This research was conducted to determine the implementation of the Dealer Management System (DMS) at PT X. This research is qualitative research with descriptive methods. The data collection techniques used were observation, interviews, documentation and literature study. During its use, the Dealer Management System (DMS) at PT X has been quite effective in supporting planning, decision making and control functions. The implementation of the Dealer Management System (DMS) at PT X has provided benefits from various operational aspects, thereby increasing efficiency and productivity.